Implementation of a Practice- and Mentoring-Based Advanced Training Program to Enhance Early Childhood Teachers’ Professional Competence - Elis Komalasari; Jhoni Warmansyah; Restu Yuningsih; Meliana Sari; Resti Yulia; Angraini Daboti; Noor Annis Azwin Binti Fakaruddin (Journal of Comunity Service in Early Childhood Education, 2025)
Background: Improving the professional competence of early childhood teachers is essential to ensure the quality of learning and child development outcomes. However, many teachers still face challenges in pedagogical skills, curriculum development, and the integration of digital media in learning. These conditions indicate the need for structured, practice-oriented training supported by field mentoring. Aims: This program aims to enhance early childhood teachers’ professional competence through a practice- and mentoring-based advanced training program. Methods: This program employed a Service Learning approach, integrating training, practical experience, and community-based application. The implementation consisted of three stages: preparation, implementation, and evaluation. The program involved 50 early childhood teachers in Padang Panjang. Activities included in-class training, independent practice assignments, field mentoring, local learning visits, and dissemination activities. Evaluation was conducted through pre- and post-tests, observation, and assessment of participants’ performance. Data were analyzed descriptively. Results: The findings show improvements in teachers’ competencies, including understanding of child development, learning strategies, curriculum design, assessment practices, and the use of digital media. Participants also demonstrated enhanced ability in lesson planning, developmental assessment, and implementing innovative learning. Mentoring and field-based activities strengthened practical skills and confidence. Conclusion: A practice- and mentoring-based advanced training program effectively improves teachers’ professional competence. The integration of training, practice, and mentoring provides meaningful and sustainable learning outcomes and can serve as a model for similar programs.